Assessing scientific literacy: a study with 9th grade students in Portugal - Coppi, Marcelo; Fialho, Isabel; Cid, Marília (Frontiers in Education, 2024)
Aiming to assess the scientific literacy level of Portuguese 9th grade students and analyse whether the variables sex, liking for the subjects of Natural Sciences and Physical-Chemistry, failure in these subjects, school socio-economic context and course option were associated to the students' scientific literacy levels, we applied the Avaliação da Literacia Científica Essencial (ALCE) instrument to 516 students. Overall, the results showed that the majority of students were at the moderate level and that 64.1% were scientifically literate. Analysing by subtest, we found that in the Nature of Science (NOS) and Impact of Science and Technology on Society (ISTS) subtests, the majority of students were at the moderate level and in the Content of Science (CS) subtest, the majority were at the low level of scientific literacy; whereas 70.0%, 72.9% and 39.9% of students were classified as scientifically literate in the NOS, ISTS and CS subtests, respectively. The greatest difficulties were concentrated in the CS subtest, particularly in Biology, Physics and Chemistry. The analysis according to the independent variables shows that the students' scientific literacy level might be associated with their liking for the subjects of Natural Sciences and Physical-Chemistry and their expectations regarding the profession they wish to pursue in the future.